Synthesis of hexagonal WO3nanowires by microwave-assisted hydrothermal method and their electrocatalytic activities for hydrogen evolution reaction - Anukorn Phuruangrat (2018)
Hexagonal WO3(hex-WO3) nanowires with high aspect ratio and crystallinity have been prepared for the first time by a microwave-assisted hydrothermal method. By using X-ray diffraction, scanning electron microscopy, transmission electron microscopy and high resolution transmission electron microscopy, the phase and morphology of the products were identified, which were controlled by reaction temperature, holding time and added salts. Uniform hex-WO3nanowires with a diameter of 5-10 nm and lengths of up to several micrometres were synthesized by a microwave-assisted hydrothermal process at 150 °C for 3 h in a solution containing (NH4)2SO4as a capping reagent and Na2WO4as a starting material. The aspect ratio and specific surface area of hex-WO3nanowires were 625 and 139 m2g-1, respectively, which represented one of the highest values reported for WO3. The electrocatalytic activity for hydrogen evolution reaction of hex-WO3nanowires was also investigated by cyclic voltammetry and linear sweep voltammetry. The results demonstrated that hex-WO3nanowires were a promising electrocatalyst for the hydrogen evolution reaction (HER) from water. © 2010 The Royal Society of Chemistry.